Mathematical substantiation of diagnostics of the technical condition of the oil pipeline - A.G. Yessengaliyev; A.D. Tapashev (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2021)
The paper is proposed a mathematical model of source recovery for the partial differential equation of parabolic type on a tree graph. The developed model makes it possible to apply the results in the diagnostics of the operation of large-scale pipelines through which liquids are pumped, in particular, the detection of a blockage in a separate link of the main oil pipeline.